Who was Amelia Earhart? Biography - Easy Reader. - Jerome, Kate Boehm, David Cain.; Cain, David, 1951- (New York : Grosset & Dunlap, 2002)
Examines the life of pioneer aviator Amelia Earhart, who mysteriously disappeared during an around-the-world flight in 1937.
Includes bibliographical references (p. 106).
Keywords: Earhart, Amelia, -- 1897-1937 -- Juvenile literature; Earhart, Amelia, -- 1897-1937.; Air pilots -- United States -- Biography -- Juvenile literature; Women air pilots -- United States -- Biography -- Juvenile literature; Air pilots; Women -- Biography